2015
DOI: 10.1038/ijir.2015.23
|View full text |Cite|
|
Sign up to set email alerts
|

Additive effects of Artemisia capillaris extract and scopoletin on the relaxation of penile corpus cavernosum smooth muscle

Abstract: The objective was to investigate the cellular effect and action mechanism of Artemisia capillaris extract (ACE) and its component, scopoletin, on penile corpus cavernosum smooth muscle (PCCSM). In vitro study with PCCSM, the precontracted PCCSM with phenylephrine was treated with ACE or scopoletin. Cyclic nucleotides in the perfusate were measured by radioimmunoassay and expression of protein and mRNA of endothelial nitric oxide synthase (eNOS) and neuronal nitric oxide synthase in the perfused PCCSM were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, we notice a highly significant increase (p < 0.01) in relative weight of ovary in G3 and G4; and significant increase (p < 0.05) in G1 compared to the control. We also observed not statistically [7] proved that the supplementation of oleic acid induces production of prostaglandin in maternal endometrial and Choi B R et al (2015) [8] reported that the perfusion with scopoletin lead to significant increase in cyclic adenosine monophosphate. It is well known that the gonadotropins FSH and LH act on their target cells via their specific membrane receptors, respectively FSHR and LHR.…”
Section: Evolution Of Organs Weightmentioning
confidence: 63%
“…However, we notice a highly significant increase (p < 0.01) in relative weight of ovary in G3 and G4; and significant increase (p < 0.05) in G1 compared to the control. We also observed not statistically [7] proved that the supplementation of oleic acid induces production of prostaglandin in maternal endometrial and Choi B R et al (2015) [8] reported that the perfusion with scopoletin lead to significant increase in cyclic adenosine monophosphate. It is well known that the gonadotropins FSH and LH act on their target cells via their specific membrane receptors, respectively FSHR and LHR.…”
Section: Evolution Of Organs Weightmentioning
confidence: 63%
“…Of the phytochemical constituents determined in leaves and stems of J. macrantha ethyl acetate fraction, some of them have demonstrated to ameliorate the ED in experimental animals. Scopoletin showed a positive effect in penile erection of rats through the NO-cGMP and adenylyl cAMP-PKA signaling pathways [ 25 ]. Vitexin at doses of 40 mg/kg regulated some endocrine hormones and had an improving in the fertility rate sex performance in diabetic mice, the mechanism involved might be in the modulation of hypothalamus–pituitary–gonadal axis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCCSM tension was measured as described previously [ 17 ]. Briefly, each rabbit PCCSM strip was mounted and equilibrated for 60 min, with an adjustment of the stretch level to a resting tension of 1 g. Then, PE (10 −5 M) was added to adjust the maximum contractile tension.…”
Section: Methodsmentioning
confidence: 99%